Ocular Findings in Children with Cerebral Palsy - Cumurcu, Tongabay; Cumurcu, Hatice Birgül; Erkorkmaz, Ünal; Yardım, Hüseyin (Fırat University, 2007)
Objective: To determine the variety and frequency of ocular problems in children with cerebral palsy (CP). Materials and Methods: A total of 46 children with CP and 50 healthy children were included in the study. The age range of the children was between 5 months and 15 years. Complete ophthalmologic, orthoptic, psychiatric and neurologic examination of all children were performed and ocular findings were classified. Results: Refractive errors were the most frequently and ocular motility disorders were the second frequently detected ocular problems, and there was a statistically significant difference between CP and control group (p

Amaç: Serebral palsi'li (SP) çocuklarda göz bulgularının sıklığını ve çeşitliliğini belirlemek. Gereç ve Yöntem: Çalışmaya SP tanısı almış 46 hasta ve kontrol grubu olarak da 50 sağlıklı çocuk dahil edildi. Hasta ve kontrol grubundaki çocukların yaşları 5 ay ile 15 yaş arası değişiyordu. Tüm çocukların komple oftalmolojik, ortoptik, psikiyatrik ve nörolojik muayeneleri yapılmış, göz bulguları sınıflandırılmıştır. Bulgular: En sık tesbit ettiğimiz göz problemi kırma kusurları, ikinci sıklıkta oküler motilite bozuklukları şeklindeydi ve SP ile kontrol grubu arasındaki fark da istatistiksel olarak anlamlı şekilde yüksekti (p
Serebral Palsili Çocuklarda Göz Bulguları